Effects of Micronutrients (Mn and Zn) Fertilizer on the Growth and Production of Sorghum (Sorghum bicolor L.) - Batubara, Siti Fatimah; Chairuman, Novia; Aryati, Vivi; Siagian, Deddy Romulo (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2023)
Micronutrients Mn and Zn are essential elements required in trace amounts, although they play an important role in plant growth. This study aimed to investigate the impact of manganese (Mn) and zinc (Zn) fertilizer on growth and productivity of sorghum. This study was conducted in farmer’s field at Pasar 6 Kwala Mencirim Village, Sei Bingai District, Langkat Regency, North Sumatera started in December 2020 until April 2021. A non-factorial randomized block design with eight treatments and four replications was used, consisted of control (without fertilizer), 100% N, P, K (local fertilizer recommendation), and the level of Mn and Zn fertilizer combined with 75% and 50% dose of N, P, K fertilizer. Measurements were taken for plant height and plant production. The data was analyzed using ANOVA and DMRT at a significance level of 5%, and RAE equation. This study showed that Mn and Zn fertilizers significantly affected sorghum growth and production. The highest productivity was 4770 kg ha-1, while the control was 2260 kg ha-1. This study concluded that applying 1 dose Mn and Zn fertilizer combined with 75% N, P, K increase the yields and reduces 25% the use of N, P, K fertilizers in sorghum field.